Manajemen Pengembangan Kurikulum 2013 Berbasis Komputer di SMPN 6 Palangka Raya - Muhammad Tri Ramdhani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Based on the results of research that has been carried out, that in 2013 the process of learning Curriculum in SMP 6 Palangka Raya could not occur regardless of the teacher as a facilitator of learning and learning devices in the form of the syllabus, RPP, methods and sources learning, as well as the media used. The methods used by teachers in teaching material of the PIE very creative as a method of discussion, demonstration, and cooperative learning. Although only a few techniques that can be applied by teachers in delivering PIES. But the methods used are already markedly, so students don't get bored in performing learning. Beside that, in taking the value with the authentic assessment that includes attitudes, knowledge, and skills is done separately or singly. Factor endowments and Pengambat in the implementation of the curriculum Learning 2013 Islamic education at SMP 6 Palangka Raya. Supporting factors among others 1) Principal Leadership, Teacher Creativity 2), 3) Facilities and learning resources, 3) a conducive environment. Then as for Penghambatnya Factors among others 1) learners, 2) assessment process, 3) Government regulation that is always changing. The solution Is to Solved Barriers in the implementation of the curriculum of Teachers must be creative, i.e., 2013, do the IHT (In House Training) between tests and assessments, Hunting through the internet as well as asked by colleagues who also attended the IHT organized by the Government.